National University Cancer Institute Singapore: Pioneering an innovative healthcare model - MACK, Daniel Z. (Institutional Knowledge at Singapore Management University, 2020)
Associate Professor Chng Wee Joo, Director of the National University Cancer Institute Singapore (NCIS), started to move the treatment of cancer patients out of the hospital to the community and patients’ homes. This innovative business model was implemented to manage the lack of space in the hospital and to reduce costs for patients. Chng also believed that an environment of strong family and community support would strengthen the morale of patients and result in fewer hospital readmissions. While Singapore had a reliable and balanced healthcare system, it faced higher healthcare expenses due to prolonged life expectancies and an ageing population just like other industrialised countries. Sedentary lifestyles, traditional diet habits and an increasingly polluted environment had led to an increase in cancer cases and cancer becoming the leading cause of death. The rising demand for cancer treatment had pushed the existing infrastructure and resources in hospitals to its limits and the shortage of hospital beds had resulted in a strategy to keep patients “out of the hospital” as long as possible. Operating under the National University Health System (NUHS) healthcare cluster, NCIS was a specialty centre designed to gain synergy by addressing all aspects of care related to the disease. With the clustering of public healthcare services in Singapore in 2017, NCIS now had the opportunity to incorporate primary care and end of life considerations in the care journey of a cancer patient. With his specialty in myeloma, a type of blood cancer, Chng led his team to focus on shifting healthcare out of the hospital and into patients’ communities and home and started experimenting to deliver treatment outside of the hospital. Chng succeeded in treating myeloma in the outpatient clinic and subsequently in the patient’s home. After the initial success, his team began working on similar projects in other type of cancers. This case is designed to allow students to think about innovation more broadly – not about the product or ‘invention’ itself, but also the value of the innovation is also dependent on how the ‘invention’ is embedded in the ecosystem and the relationships and arrangements among the stakeholders.